Degradation of water protection function of the Western Caucasus mountain oakeries as a result of fellings - Bitukov, Nikolay A.; Shagarov, Lev M. (Nature Conservation Research: Заповедная наука, 2017)
The article analyses the effect of fellings for primary use on the disturbance of the water protection function of sessile oak (Quercus petraea) forests in the Western Caucasus. The study is based on long-term monitoring of spring runoff in catchments with experimental fellings in the Forest and Hydrological Station «Gorsky» (Tuapse District, Krasnodarsky Krai). It has been established that over a 28-year period after the experimental fellings, the stabilisation of runoff conditions has never come. The runoff in oak forests is mostly impacted by clear-cuttings with tractor harvesting technology. Over 30 years after clear-cutting, the spring runoff has increased on an average by 1.46 times, with a maximum increase (by 2.5 times) being observed for the first two years after cutting. In areas with group fellings, the runoff regime is generally similar to that of the control catchment for the same period.